2019
DOI: 10.1016/j.aim.2019.106815
|View full text |Cite
|
Sign up to set email alerts
|

Analytic geometry over F1 and the Fargues-Fontaine curve

Abstract: This paper develops a theory of analytic geometry over the field with one element. The approach used is the analytic counter-part of the Toën-Vaquié theory of schemes over F1, i.e. the base category relative to which we work out our theory is the category of sets endowed with norms (or families of norms). Base change functors to analytic spaces over Banach rings are studied and the basic spaces of analytic geometry (like polydisks) are recovered as a base change of analytic spaces over F1. We end by discussing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…Also we have the following foundations. First we have from [BBBK,Proposition 1.6] the Banach completion on the Banach sets over some Banach ring R which is the left adjoint functor of the inclusion:…”
Section: ∞-Categorical Completion and ∞-Categorical Solidificationmentioning
confidence: 99%
“…Also we have the following foundations. First we have from [BBBK,Proposition 1.6] the Banach completion on the Banach sets over some Banach ring R which is the left adjoint functor of the inclusion:…”
Section: ∞-Categorical Completion and ∞-Categorical Solidificationmentioning
confidence: 99%
“…We recall that a normed set is a set S equipped with a map | • | S : S → [0, ∞), and NSet denotes the category of normed sets and bounded maps. See [BBK19] §1 for more details about this category. For an S ∈ NSet, we put S + ≔ {s ∈ S | s S > 0}.…”
Section: Homological Algebra For Discrete Banach Modulesmentioning
confidence: 99%
“…The richness of this theory comes from the structure of C as a complete valued field with respect to the standard absolute value. In the authors' recent work [BM21], it has been shown that the theory of C * -algebras has a nice description in terms of the derived analytic geometry introduced in [BK17], [BB16], [BBK19] and [BK20]. Therefore, it is natural to ask what happens when the continuous C-valued functions on X are replaced by the Banach algebra C(X, R) of continuous functions valued on other Banach rings.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…In this section, we recall the basic properties of the quasi-Abelian category of Banach modules and recall the foundation of the derived analytic geometry as discussed in [BB16], [BK17], [BBK19], and [BK20].…”
Section: Preliminariesmentioning
confidence: 99%
“…This approach has been recently developed in the series of papers (cf. [BB16], [BK17], [BBK19], and [BK20]). Once the notions of derived categories and derived functors are correctly extended to the analytic setting, it is natural to consider the derived variant of Tate's acyclicity.…”
Section: Introductionmentioning
confidence: 99%